Analisis Kadar Senyawa Fitokimia pada Tumbuhan Sisal (Agave sisalana L) dengan Metode GC-MS (Gas Chromatography-Mass Spectometry) dan Aktivitas Antioksidan - Malau, Merrys Ance Rianiati; Wirawan, I Gede Putu; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024), 2024)
Analysis of Phytochemical Compound Levels in Sisal Plants ( Agave sisalana L) Using the GC-MS ( Gas Chromatography - Mass Spectometry ) Method and Antioxidant Activity. Sisal ( Agave sisalana L) is one of the natural fiber-producing plants in Indonesia. Sisal juice contains an enzyme that functions as a milk coagulant similar to that found in pineapple and papaya leaves. The Sisal plant juice as a clotting agent is still very rarely used because of public ignorance of what content is contained in Sisal juice. The purpose of this study was to determine the content of phytochemical compounds and antioxidant content of sisal extract ( Agave sisalana L). Extraction was carried out using a maceration method using 96% ethanol solvent then the maceration results were evaporated using a rotary evaporator to produce a thick extract. The thick extract was then analyzed for secondary metabolite content by phytochemical screening and using GC-MS (gas chromatography-mass spectrometry). Antioxidant activity testing was carried out using the DPPH method. The results showed that sisal phytochemical screening analysis contained alkaloid, steroid, phenolic, saponin, and tannin compounds. Terpenoid compounds were not identified in sisal plant extracts due to the absence of color changes when given a reagent solution. From the results of GC-MS analysis based on the chromatogram, there is one most dominant peak seen from the percentage of area of 30.77%. The compound is Alanylglycine, Acetamide, 2,2,2-trifluoro-, 1-Octadecanamine, N-methyl-. Antioxidant activity test using DPPH method obtained an IC50 value of 141.83 mg/ml which is classified as weak.